A linearized thermometer circuit employing a thermistor and a diode as probing elements (2003)
The development of a linearized thermistor-based thermometer circuit with a thermistor and a diode as the temperature probing elements is here reported. The circuit is effectively that of an op amp based logarithmic amplifier, which takes its input from another inverting op amp circuit having a thermistor in its feedback loop. The performance of the circuit is demonstrated experimentally and has been found to have a linearity error of less than 0.2%. The accuracy analysis of the circuit is also discussed.